KONTRIBUSI PENDIDIKAN AGAMA ISLAM DALAM PENCEGAHAN KENAKALAN REMAJA - Muhajarah, Kurnia (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2018)
Juvenile delinquency becomes a phenomenon in this life. The emergence of juvenile delinquency is influenced by various life factors that involve himself, his family and his environment. There have been many studies that examine the juvenile delinquency. This paper will discuss two main questions namely: what factors cause juvenile delinquency and how the contribution of Islamic Education (PAI) in preventing juvenile delinquency. The method used in this paper is literature study that is directed to answer the above questions. The answer is parsed by the deepening of the material by method of content analysis, hope the data obtained with the depth of material and things that surround it.The results of the study of this paper show that, First, juvenile delinquency is caused by self-adolescent factors (internal) and the environment (external). External factors that cause juvenile delinquency are families, less harmonious marital relationships, the environment, and schools, including teachers, lessons, school tasks, learning methods. Second, PAI has two contributions in preventing juvenile delinquency, namely PAI able to form a religious adolescent personality, so far from the world of juvenile delinquency and PAI able to provide space for adolescents in positive expression embodied in the balance of understanding the material of religion and knowledge.